2007
DOI: 10.1007/s11094-007-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active lignans in extract and seeds of Schizandra chinensis

Abstract: A method for standardization of Schisandra chinensis has been developed, which is based on the isolation of the pure lignan fraction with the major content of schizandrol A followed by quantitative spectrophotometric assay with reference to a reliable standard. Solutions used for the primary assay were concentrated and studied by TLC (qualitative analysis). It is established that the content of pure lignans in the S. chinensis extract varies within 0.1 -0.2%. Exhaustive extraction with a sequence of solvents s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Earlier studies found that the schizandrol A content in the tincture and in the oil extract were approximately identical at about 0.09% [6]. Table 3 gives results from quantitative analysis of total lignans in the tincture, the oil extract, and in raw material.…”
Section: Preparation Of Standard Schizandrol a Solutionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier studies found that the schizandrol A content in the tincture and in the oil extract were approximately identical at about 0.09% [6]. Table 3 gives results from quantitative analysis of total lignans in the tincture, the oil extract, and in raw material.…”
Section: Preparation Of Standard Schizandrol a Solutionmentioning
confidence: 97%
“…Exhaustive extraction of Chinese magnolia-vine seeds by various extractants [hexane, ethylether, ethanol (96% and 20%)] was used earlier to establish that the content of total lignans calculated as schizandrol A varied from 0.6 to 1.3% and averaged 1% [6] whereas the content of total lignans in the tincture was~0.2% with schizandrol A content 0.088% (HPLC) [6].…”
mentioning
confidence: 99%